Characteristics, Management, and Outcomes of Patients Hospitalized for Heart Failure in China: The China PEACE Retrospective Heart Failure Study - Yu, Yuan; Gupta, Aakriti; Wu, Chaoqun; Masoudi, Frederick A.; Du, Xue; Zhang, Jian; Krumholz, Harlan M.; Li, Jing (Journal of the American Heart Association, 2019)
Background Heart failure (HF) is an emerging epidemic in China and accounts for significant healthcare resource utilization in the inpatient setting. To create evidence-based, life-saving, and cost-saving hospitalization systems, the first step is to characterize the contemporary national landscape of inpatient HF care. Methods and Results In the China PEACE 5r-HF study (China Patient-centered evaluative Assessment of Cardiac Events Retrospective Study of Heart Failure), we used 2-stage random sampling to create a nationally representative cohort of 10 004 admissions for HF from 189 hospitals in 2015 in China. Data on patient characteristics, management, and outcomes were obtained through centralized medical record abstraction. The median age of the cohort was 73 years (interquartile range, 65-80), and 48.9% were women. More than half (56.2%) of the patients were hospitalized in rural areas. Prevalence of ejection fraction ≥50%, 40% to 50%, and <40% was 60.3%, 17.7%, and 22.0%, respectively. We identified substantial gaps in care, including underutilization of diagnostic tests such as echocardiograms (63.6%), chest imaging (75.2%), and biomarker testing (56.4%), low prescription rates of guideline-recommended medications during hospitalization and at discharge, suboptimal rates of follow-up appointments (24.3%), and widespread utilization of traditional Chinese medicine (74.8%). The combined rate of in-hospital mortality and treatment withdrawal in our study was 3.5%, and median length-of-stay was 9 days (interquartile range, 7-13). Conclusions Patients admitted with acute HF in China have distinctive epidemiology and receive substandard care, but have low inpatient mortality despite long length of stay. These findings provide opportunities for streamlining efficiencies while improving quality of inpatient HF care in China. Clinical Trial Registration URL: https://www.clinicaltrials.gov. Unique identifier: NCT02877914.